Prophylactic abdominal aorta balloon occlusion during caesarean section: a retrospective case series. (August 2016) - Wei, Xin; Zhang, Jie; Chu, Qinjun; Du, Yingying; Xing, Na; Xu, Xiaohan; Zhou, Yinhui; Zhang, Wei
Highlights: Abdominal aortic balloon occlusion was used in 45 cases of abnormal placentation. Mean estimated blood loss was 835 mL [range 200–6000 mL]. Eleven patients required blood transfusion of a mean of 1.7 units. Subtotal hysterectomy was performed in four cases. Complications included one case of arterial thrombosis and one of ischaemic femoral nerve injury. Abstract: Background: The management of patients with morbidly adherent placenta has been described using vascular balloon catheters placed in the iliac arteries, but rarely in the aorta. This case series presents our experience with prophylactic lower abdominal aorta balloon occlusion in 45 women. Methods: The records of patients in our centre who underwent caesarean section between May 2013 and June 2014 were retrospectively analysed for the use of prophylactic lower abdominal aorta balloon occlusion. Results: Forty-five cases were identified. All patients had a morbidly adherent placenta, including placenta accreta ( n =22), placenta increta ( n =20) and placenta percreta ( n =3). A subtotal hysterectomy was performed in four cases. Eleven of the 45 patients received red blood cell transfusion of a mean of 1.7 units. Mean preoperative and postoperative haemoglobin concentrations were 10.1 g/dL and 9.4 g/dL, respectively. Mean estimated blood loss was 835 mL [range 200–6000 mL]. The incidence of complications was 4.4% (2/45), including one case of lower extremity arterial thrombosis and one case of ischaemic injury to the femoral nerve. Follow up at one year was completed in 22 patients at which time all babies were well. Conclusions: Prophylactic lower abdominal aorta balloon occlusion has the potential to reduce intraoperative blood loss, transfusion and hysterectomy rate in patients with morbidly adherent placenta undergoing caesarean section. Careful patient selection is critical as the technique may be associated with potentially serious complications.